Factors associated with open air defecation in a rural field practice area of a medical college: a cross sectional study - Taranum, Arshiya; Reddy, Satya; G., Muhammed Muntazeem; Kurre, Bhaskar (International Journal Of Community Medicine And Public Health, 2020)
Background: Open defecation is the practice where people go out in fields, bushes, forests, open bodies of water or other open spaces rather than using the toilet to defecate. The health hazards due open air defecation are soil and water pollution, contamination of foods and propagation of flies which results in the spread of diseases like typhoid, cholera, dysenteries, diarrheas, hookworm diseases, ascariasis, viral hepatitis and other intestinal infections. Methods: A cross sectional study was conducted at Singanodi village. 122 houses were selected for interview. One member from each household, preferably the head of the family was interviewed. The questionnaire included the socio-demographic features, practices about sanitary latrine usage and awareness about the diseases due to open air defecation. Data was entered in MS Excel and analysed using SPSS vs 20. Results: In the study the prevalence of open air defecation was found to be 63.1%. Majority of the study participants (52.5%) had sanitary latrines in their houses. 15.6% of the household practices open air defecation in spite of having toilets in their homes. Significant association was found between education and overcrowding with open air defecation. Conclusions: The study reinforces the importance of creating awareness about the importance of sanitary latrines and involvement of Government, NGO and communities is essential to stop open air defecation practices.